Evaluating the Organizational Interoperability Maturity Level in ICT Research Center - Manijeh Haghighinasab; Samiyeh Khosravi (Journal of Information Technology Management)
Interoperability refers to the ability to provide services and to accept services from other systems or devices. Collaborative enterprises face additional challenges to interoperate seamlessly within a networked organization. The major task here is to assess the maturity level of interoperating organizations. For this purpose the maturity models for enterprise were reviewed based on vendors’ reliability and advantages versus disadvantages. Interoperability maturity model was deduced from ATHENA project as European Integrated Project in 2005, this model named as EIMM was examined in Iran information and Communication Institute as a leading Telecommunication organization. 115 questionnaires were distributed between staff of 4 departments: Information Technology, Communication Technology, Security and Strategic studies regarding six areas of concern: Enterprise Modeling, Business Strategy Process, Organization and Competences, Products and Services, Systems and Technology, Legal Environment, Security and Trust at five maturity levels: Performed, Modeled , Integrated, Interoperable and Optimizing maturity. The findings showed different levels of maturity in this Institute. To achieve Interoperability level, appropriate practices are proposed for promotion to the higher levels.